Life history of Chrysozephyrus alienus (Koiwaya & Monastyrskii, 2010) (Lepidoptera) in central Vietnam - Hasegawa, Takashi; Saito, Kotaro; Lien, Vu Van; Miyagawa, Takashi; Kubota, Akiko; Yokochi, Takashi (Academia Journal of Biology, 2017)
We have successfully reared the larvae of Chrysozephyrus alienus (Koiwaya & Monastyrskii, 2010), and presented the life history of this species. The larval foodplant was found to be Lyonia ovalifolia var. pubescens. The tactile setae of the 1st instar larvae are absent at dorsal anterior area at the 1st abdominal segment and dorsal area at the 7th abdominal segment. The pattern is rather similar to that of Chrysozephyrus scintillans. Citation: Hasegawa T., Saito K., Vu Van Lien, Miyagawa T., Kubota A., Yokochi T., 2017. Life history of Chrysozephyrus alienus (Koiwaya & Monastyrskii, 2010) (Lepidoptera) in central Vietnam. Tap chi Sinh hoc, 39(3): 291-295. DOI: 10.15625/0866-7160/v39n3.9348. *Corresponding author: airsjapan64@gmail.com Received 20 March 2017, accepted 20 August 2017